POSSIBILITIES OF VISUAL ELECTRONIC EDUCATIONAL PUBLICATIONS IN THE FORMATION OF PROFESSIONAL QUALIFICATIONS OF BACHELORS IN THE FIELD OF SERVICE (American Journal of Pedagogical and Educational Research, 2023)
Of great importance is the electronic presentation, which reflects the recent achievements of the main activities of digital education, the collection of large volumes of digital data, the production of Science, Technology, Engineering. During the study, we noted that many teachers used inappropriate information presented on the screen using pedagogical electronic products.